1993
DOI: 10.1111/j.1365-2044.1993.tb07599.x
|View full text |Cite
|
Sign up to set email alerts
|

The anaesthetic management of patients with dystrophic epidermolysis bullosa

Abstract: SummaryThe case notes and anaesthetic charts of 44 patients with dystrophic epidermolysis bullosa were reviewed retrospectively. A total qf 390 general anaesthetics were performed for 469 Key wordsComplications; dystrophic epidermolysis bullosa. Anaesthesia.Dystrophic epidermolysis bullosa (DEB) is a rare, hereditary mucocutaneous disorder whose primary feature is the formation of blisters following minor shearing trauma to the skin. Treatment of DEB involves surgery which has a number of challenging implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 28 publications
1
58
0
Order By: Relevance
“…Although the results of both types of surgical procedures are reported as successful, they are both major surgical procedures with considerable morbidity and mortality and should be performed in extensive esophageal involvement [5,7]. General anesthesia, which is mandatory during surgical procedures or endoscopic bougienage, is another problem in RDEB because of upper respiratory tract involvement and risk of perforation during intubation [14].…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of both types of surgical procedures are reported as successful, they are both major surgical procedures with considerable morbidity and mortality and should be performed in extensive esophageal involvement [5,7]. General anesthesia, which is mandatory during surgical procedures or endoscopic bougienage, is another problem in RDEB because of upper respiratory tract involvement and risk of perforation during intubation [14].…”
Section: Discussionmentioning
confidence: 99%
“…Second, total intravenous anesthesia with spontaneous breathing preserved was another possible choice. Griffin and Mayou [3] reported that only 7% of 469 surgical patients with DEB received intravenous ketamine anesthesia and 3% received propofol. However, they did not describe the anesthetic methods in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Where intubation is deemed difficult, an awake oral or nasal fibreoptic intubation is appropriate. 21 The use of a laryngeal mask airway (LMA) has been described. 21 This technique could potentially cause damage to the pharyngeal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…21 The use of a laryngeal mask airway (LMA) has been described. 21 This technique could potentially cause damage to the pharyngeal mucosa. If an LMA is to be used, it should be very well lubricated and inserted with care to avoid mucosal damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation